Usability and User Experience Evaluation on Extracurricular Website (SINEMA) Implementation using SUS and UEQ Methods - AKBAR, MUHAMMAD; Wirdayanti; Sabarudin Saputra; Deni Luvi Jayanto; Sri Khaerawati Nur; Nouval Trezandy; Bakri (Information Technology International Journal, 2025)
The rapid integration of web-based platforms in higher education highlights the importance of usability and user experience in supporting students’ extracurricular activities. This study evaluates the usability and user experience of the Student Extracurricular Information System (SINEMA) developed at Tadulako University. A total of 99 respondents participated, selected from a population of 5,581 active users through Slovin’s formula. Two standardized instruments were applied: the System Usability Scale (SUS) to capture global usability perceptions and the User Experience Questionnaire (UEQ) to assess six dimensions of user experience. The SUS results indicate a mean score of 76.06, which falls within Grade B and the “Good” category, exceeding the global benchmark. This suggests that the system is generally usable, although certain respondents reported minor challenges requiring further improvement. The UEQ results show that Perspicuity (1.94), Dependability (1.94), and Stimulation (1.93) achieved the “Excellent” category, reflecting clarity, reliability, and engagement. Meanwhile, Attractiveness (1.65), Efficiency (1.58), and Novelty (1.72) were rated “Good,” highlighting positive perceptions but also opportunities for optimization. Overall, the findings demonstrate that SINEMA effectively supports extracurricular management with satisfactory usability and strong user experience. The study contributes novelty by integrating SUS and UEQ for comprehensive evaluation within a higher education extracurricular context. Recommendations include enhancing efficiency and novelty to elevate user satisfaction and system adoption.